Structural, functional and evolutionary diversity of 4-coumarate-CoA ligase in plants - Lavhale, Santosh G.; Kalunke, Raviraj M.; Giri, Ashok P. (Planta, 2018)
Main conclusions The 4-coumarate-CoA ligases (4CL) contribute in channelizing flux of different phenylpropanoid biosynthetic pathways. Expression of 4CL is optimized at developmental stages and in response to environmental triggers such as biotic and abiotic stresses. The enzyme is valuable in metabolic pathway engineering for curcuminoids, resveratrol, biofuel production and nutritional improvement. Vigorous analysis of regulation at functional and expression level is obligatory to attain efficient commercial production of candidate metabolites using 4CL. Phenylpropanoid pathway provides precursors for numerous secondary metabolites in plants. In this pathway, 4-coumarate-CoA ligase (EC 6.2.1.12, 4CL) is the main branch point enzyme which generates activated thioesters. Being the last enzyme of three shared common steps in general phenylpropanoid pathway, it contributes to channelize precursors for different phenylpropanoids. In plants, 4CL enzymes are present in multiple isoforms and encoded by small gene family. It belongs to adenylate-forming enzyme family and catalyzes the reaction that converts hydroxy or methoxy cinnamic acid derivatives to corresponding thioesters. These thioesters are further utilized for biosynthesis of phenylpropanoids, which are known for having numerous nutritional and medicinal applications. In addition, the 4CL enzymes have been characterized from various plants for their role in plant physiology or in biotic and abiotic stresses. Furthermore, specific isoforms are differentially regulated upon exposure to diverse stimuli leading to flux diversion toward the particular metabolite biosynthesis. Evolutionary studies showed that 4CL separately evolved after monocot and dicot segregation. Here, we provide a comprehensive review on 4CL, which includes evolution, function, gene/protein structure, role in metabolite biosynthesis and cellular partition, and their regulation. Based on the available data, we have explored the scope for pathway engineering by utilizing 4CL enzymes.

Terpene profiling, transcriptome analysis and characterization of cis–terpineol synthase from Ocimum - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Dholakia, Bhushan B.; Lavhale, Santosh G.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Physiology and Molecular Biology of Plants, 2019)
Ocimum species produces a varied mix of different metabolites that imparts immense medicinal properties. To explore this chemo-diversity, we initially carried out metabolite profiling of different tissues of five Ocimum species and identified the major terpenes. This analysis broadly classified these five Ocimum species into two distinct chemotypes namely, phenylpropanoid-rich and terpene-rich. In particular, -caryophyllene, myrcene, limonene, camphor, borneol and selinene were major terpenes present in these Ocimum species. Subsequently, transcriptomic analysis of pooled RNA samples from different tissues of Ocimum gratissimum, O. tenuiflorum and O. kilimandscharicum identified 38 unique transcripts of terpene synthase (TPS) gene family. Full-length gene cloning, followed by sequencing and phylogenetic analysis of three TPS transcripts were carried out along with their expression in various tissues. Terpenoid metabolite and expression profiling of candidate TPS genes in various tissues of Ocimum species revealed spatial variances. Further, putative TPS contig 19414 (TPS1) was selected to corroborate its role in terpene biosynthesis. Agrobacterium-mediated transient over-expression assay of TPS1 in the leaves of O. kilimandscharicum and subsequent metabolic and gene expression analyses indicated it as a cis–terpineol synthase. Overall, present study provided deeper understanding of terpene diversity in Ocimum species and might help in the enhancement of their terpene content through advanced biotechnological approaches.
Keywords: Agro-infiltration assay; Metabolite profiling; Ocimum; Terpene synthase; Terpenes; Transcriptome

Functional insights into two Ocimum kilimandscharicum 4-coumarate-CoA ligases involved in phenylpropanoid biosynthesis - Lavhale, Santosh G.; Joshi, Rakesh S.; Kumar, Yashwant; Giri, Ashok P. (International Journal of Biological Macromolecules, 2021)
Plant 4-coumarate-CoA ligase (4CL) catalyzes the ligation of CoA to cinnamic acid and its derivatives. Activated CoA esters are utilized for the biosynthesis of phenolic metabolites and lignin that play essential function in plants. Here, we characterize the diversity of Ocimum kilimandscharicum 4CLs (Ok4CLs). Phylogenetic analysis suggest that Ok4CLs could be grouped into three classes, class I -enzymes mostly involved in lignin biosynthesis, class II -non-structural phenylpropanoid biosynthesis and class III -yet to be characterized for specific role(s). We selected two Ok4CLs namely Ok4CL7 and Ok4CL15 for further characterization. Gene expression analysis sug-gested that Ok4CL7 is highly expressed in leaf trichomes, whereas Ok4CL15 is abundant in the roots. The recom-binant Ok4CL7 and Ok4CL15 had optimal enzyme activities at 40 degrees C in pH 8 and 7, respectively. Ok4CL7 showed substrate preference towards p-coumaric acid, ferulic acid and caffeic acid. While, Ok4CL15 preferredp-coumaric acid, ferulic acid and sinapic acid. Feruloyl adenylate showed higher number of contacts and lowers binding en-ergy with Ok4CL7 and 15 compared to cinnamoyl adenylate. Based on root-specific expression and preference for sinapic acid, Ok4CL15 might be involved in lignin biosynthesis. Further exploration is needed to unravel the role of diverse Ok4CLs in O. kilimandscharicum. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: 4-Coumarate-CoA ligase; Flavonoids; lignin; Ocimum kilimandscharicum; Phenylpropanoids

Ocimum kilimandscharicum 4CL11 negatively regulates adventitious root development via accumulation of flavonoid glycosides - Lavhale, Santosh G.; Kondhare, Kirtikumar R.; Sinthadurai, Veenothini S.; Barvkar, Vitthal T.; Kale, Rutuja S.; Joshi, Rakesh S.; Giri, Ashok P. (Plant Journal, 2024)
4-Coumarate-CoA Ligase (4CL) is an important enzyme in the phenylpropanoid biosynthesis pathway. Multiple 4CLs are identified in Ocimum species; however, their in planta functions remain enigmatic. In this study, we independently overexpressed three Ok4CL isoforms from Ocimum kilimandscharicum (Ok4CL7, -11, and -15) in Nicotiana benthamiana. Interestingly, Ok4CL11 overexpression (OE) caused a rootless or reduced root growth phenotype, whereas overexpression of Ok4CL15 produced normal adventitious root (AR) growth. Ok4CL11 overexpression in N. benthamiana resulted in upregulation of genes involved in flavonoid biosynthesis and associated glycosyltransferases accompanied by accumulation of specific flavonoid-glycosides (kaempferol-3-rhamnoside, kaempferol-3,7-O-bis-alpha-l-rhamnoside [K3,7R], and quercetin-3-O-rutinoside) that possibly reduced auxin levels in plants, and such effects were not seen for Ok4CL7 and -15. Docking analysis suggested that auxin transporters (PINs/LAXs) have higher binding affinity to these specific flavonoid-glycosides, and thus could disrupt auxin transport/signaling, which cumulatively resulted in a rootless phenotype. Reduced auxin levels, increased K3,7R in the middle and basal stem sections, and grafting experiments (intra and inter-species) indicated a disruption of auxin transport by K3,7R and its negative effect on AR development. Supplementation of flavonoids and the specific glycosides accumulated by Ok4CL11-OE to the wild-type N. benthamiana explants delayed the AR emergence and also inhibited AR growth. While overexpression of all three Ok4CLs increased lignin accumulation, flavonoids, and their specific glycosides were accumulated only in Ok4CL11-OE lines. In summary, our study reveals unique indirect function of Ok4CL11 to increase specific flavonoids and their glycosides, which are negative regulators of root growth, likely involved in inhibition of auxin transport and signaling.
Keywords: 4-Coumarate-CoA ligase; 7-O-bis-alpha-l-rhamnoside; adventitious root; auxin transport; Flavonoids; kaempferol-3; Ocimum kilimandscharicum; quercetin-3-O-rutinoside; rootless

Rootless survivors in plants - Kondhare, Kirtikumar R.; Lavhale, Santosh G.; Giri, Ashok P. (Plant Science, 2026)
The root system provides anchorage, uptakes of nutrients and water, and forms different associations within soil environments that govern plant fitness, crop performance, and yield. Auxin controls almost all aspects of root development. Both shoot- and root-derived auxins contribute to formation of polar auxin transport, which is crucial for establishing and maintaining normal root architecture. The coordinated activities of auxin influx and efflux carriers establish necessary polar auxin transport. A variety of natural metabolites and synthetic compounds are shown to interfere with auxin metabolism, transporters and signaling pathways having a negative impact on root growth. In this review, we highlight the reports demonstrating the observance of rootless phenotypes in plants and associated molecular mechanisms. Rootless phenotypes can be produced under in vitro culture conditions by modulation of phytohormone combinations (especially auxin and cytokinin), and supplementation of naturally-occurring flavonoids and their glycosides or synthetic auxin transport inhibitors (1-Nnaphthylphthalamic acid and 2,3,5-triiodobenzoic acid) or under in vivo conditions by modulation of several genes directly or indirectly associated with auxin biology. Further, we describe the crosstalk of naturallyoccurring flavonoids (e.g. kaempferol, quercetin), their glycosides, and other metabolites (e.g. azelaic acid, cis-cinnamic acid) with auxin transporters, their mobile nature, and influence on root development. Moreover, we provide evolutionary perspective on the auxin and flavonoid pathways and their possible roles in naturally rootless plants. We also emphasize the importance of rootless or reduced root growth phenotypes in modern agriculture, and the pressing needs to utilize naturally occurring auxin transport inhibitors for industrial and research applications.
Keywords: Auxin; Flavonoid; Flavonoid-glycoside; Polar auxin transport; rootless